INSTITUTIONAL CONTEXT OF GENERAL ELECTIONS COMMISSION AND THE IMPLEMENTATION OF THE 2024 ELECTION - Jurdi, Syarifuddin (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2022)
This article explains the General Elections Commission (KPU) institution in facing the 2024 General Election (Pemilu). The main aims to understand the process of forming an election management body and its institutional transformation as well as the readiness of the KPU in facing the 2024 simultaneous elections. This paper tends to use verstehen analysis which developed by Weber, to look within the institution and slightly oriented towards phenomenological analysis developed by Berger and Luckmann. This research employs genealogical perspective as theoretical perspective. In general, this article concludes that to hold clean election, independent and credible institutions are needed. Therefore; First, it is necessary to strengthen the capacity, technical capabilities and the substance of election organizers, support from human resources with integrity is needed to produce elections with dignity; Second, the readiness of regulations and policies related to all stages of the election and election program can be carried out in accordance with the regulations and stages that govern them; Third, strengthening the organizing institutions to encourage voter participation through outreach and voter education in order to have critical, intelligent voters, and those who reject money politics, not easily mobilized and anti-hoax.